Implementación de contabilidad comercial en “Promusa Electrodomésticos” en la ciudad de Yantzaza, período: noviembre y diciembre de 2015 - Cabrera Zúñiga, Andreina Cecibel (2016)
The “IMPLEMENTATION OF COMMERCIAL ACCOUNTING IN "PROMUSA APPLIANCES" IN THE CITY OF YANTZAZA, PERIOD: NOVEMBER AND DECEMBER 2015" aims to develop an accounting process for the permanent inventory system for financial statements that facilitate decisions that improve the economic performance of the company. In addition you will be complying with one of the requirements arranged in the current academic regime at the Universidad Nacional de Loja regulations for obtaining the degree of engineer in accounting and auditing, counter public Auditor. Pursuant to the objectives was to organize the documentation and proof of support that facilitated the gathering of information, proceeded to carry out the inventory of assets, values and obligations that the company, State of initial situation that allowed to discover the assets, liabilities, and equity at the beginning of the year, was designed a Plan and Manual of accounts for the registration of transactions daily in the journal book then developed the ledger, Trial Balance, all this process made it possible to draw up the financial statements and concluded with the application of financial indicators to be submitted to the owner of the commercial so you have a clear view of the economic situation of your business. Under these conditions, and at the end of the accounting process was concluded in general as the commercial accounts it will allow to organize and control the resources of the commercial, improve the profit of the same and for greater profits, it is recommended its use and application to achieve efficiency and effectiveness in the provision of services to its customers.